Neprijatelj bez lica: ideološka i umetnička percepcija drugog (Philologia, 2021)
Ideological discourse often tends to generalize and dehumanize the Other: especially in wartime and other situations of political confrontation, causality may be discerned between obfuscating language and imagery regarding the ‘faceless enemy’ and insensitively inﬂicting pain and destruction on him. One possible way of counteracting the tragic effect of such ideological reductions is by resorting to creative imagination. Barker’s Scenes from an Execution and a number of critical studies are analysed in order to examine this possibility and suggest a relevant course of action. Our habitual recourse to conceptual logic, which, according to Ransom, is psychologically founded on the ego’s need for mastery, is juxtaposed to the metaphorical, poetic activity of the mind, deepening perception and keeping cognition open-ended. This binary opposition is further examined by Darko Suvin, who calls for fusing the lessons of political and poetic practice with a view to preserving the awareness of the Other’s humanity. However, it is important to acknowledge the universality of the problem and proceed to deconstruct dehumanizing ideological concepts worldwide and impartially: for to accuse only our ‘enemies’ of producing them would be to sustain this self-same dynamic
Keywords: ideologija; neprijatelj; Drugo; percepcija; ego; imaginacija; metafora; čulnost; saosećanje; kognicija